Pengaruh Edukasi Media Platform Tiktok Terhadap Pengetahuan Penderita Hipertensi di Wilayah Kerja Puskesmas Cireunghas - Rika Rahayu; Irawan Danismaya; Arfatul Makiyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Hypertension is still a significant problem in the global health sector today. The general public recognizes this condition as